Satisfacción de las usuarias de control prenatal en el servicio de ginecología y obstetricia del Centro de Salud San Martín de Porres de la ciudad de Machala 2015-2016. - Carchipulla Toala, Angie Mercedes (2016)
The following research has as an objective to determine the degree of satisfaction from the female users who attend to prenatal control, the quality of the service that is given and if they accomplish with the approaches set out by the regulatory component from the mother country. This is a descriptive design; whose unit of analysis are the female users who come to Gynecology and Obstetrics service, a number of 101 users was established in order to perform the survey; using an instrument to evaluate the satisfaction of the user the same that was elaborated by the National Bureau of Statistics and Analysis of Health Information the same that allowed us to have a better diagnose about the perception of satisfaction in this Health Center. The most relevant results show that, 51% of the people surveyed feel satisfied with the waiting time and they also consider it acceptable. Other factors related with the quality of attention like if the professional examined her 67%, infrastructure 72.9%, attention by trained personnel 100%, proper assessment 89.1%, warmth attention 88.1% this percentages are reflected in the satisfaction from the users (female) and compliance with the regulatory approaches for the attention of pregnant. KEY-WORDS: degree of satisfaction from female users, quality and prenatal care.